Developing Wide Flexible Robust PWM Driver by Flip Flop For Supporting The SMPS Technology - Augustinus Sujono; Feri Adriyanto; Hari Maghfiroh; Joko Slamet Saputro; Agus Ramelan (Universitas Sebelas Maret (UNS), 2020)
The limitation of the operational area of the PWM signal generator provided by the microprocessor or chip, give the opportunity to develop flip flop technology that has been widely used in digital technology as a latch, counter, register, memory and so on, will be able to be developed into a PWM driver. Flip flop technology has developed and is able to reach a very wide operational area regarding voltage and frequency variations. So in this research flip flop technology was developed as a PWM signal driver and the results were better, involving the ability to vary voltage from 6 to 60 Volts, frequencies from 2 to 81 kHz and duty cycles of 10 -75%. Furthermore, if a component with higher capability is selected, it will be able to operate in very low to very high operating areas, exceeding the capabilities of the microprocessor or chip.